Understanding Other Cultures - Brown Corinne Ina (Prentice Hall, 1963)
This book has been written for the general reader to clarify the hows and whys of the many cultures which surround us. Man and Culture, The Work of the World, How People Live Together, From Birth to Death, The Embroidery of Life, How Do They Define It, The System of Values, Religion in Culture, The Long Road, Peoples in Transition, Notes and References, Bibliography.